1999
DOI: 10.1097/00002030-199909100-00021
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and psychological variables influencing adherence to antiretroviral therapy

Abstract: Sociodemographic and psychological factors influence the degree of adherence to antiretroviral therapy. Overall, IVDUs and younger individuals tend to have a poorer compliance, as well as subjects with depression and lack of self-perceived social support. An increased awareness of these factors by practitioners attending HIV-infected persons, recognizing and potentially treating some of them, should indirectly improve the effectiveness of antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
335
12
31

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 568 publications
(418 citation statements)
references
References 30 publications
40
335
12
31
Order By: Relevance
“…In the present study, adequate adherence was considered to be the use of at least 90% of the prescribed medications 10,17 , taking into account the previous five days as a proxy of habitual behavior. The frequency of non-adherence was 25.73%, similar to the figure found in a study conducted in 60 outpatients services located in seven states of Brazil 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, adequate adherence was considered to be the use of at least 90% of the prescribed medications 10,17 , taking into account the previous five days as a proxy of habitual behavior. The frequency of non-adherence was 25.73%, similar to the figure found in a study conducted in 60 outpatients services located in seven states of Brazil 25 .…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the sample size, the frequency of exposure was based on two variables studied by GORDILLO et al 10 . The sample size estimated was 352 patients for the mode of HIV transmission variable and 372 for the current work situation variable.…”
Section: Methodsmentioning
confidence: 99%
“…The data collection considered participants who missed at least one dose in the past month as being non-adherent to ART [30,31]. …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, multiple linear regressions examined the association between harmful alcohol drinking and the quality of life (QOL) domains. In each model, important covariates such as age, education, marital status, occupation, physical symptoms, and HIV-clinical staging were adjusted, as studies have indicated that these factors can influence ART adherence [30,31]. All data were analyzed using STATA version 12.1.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the behavioral consequences of depression among patients with HIV/AIDS have significant health implications, including problems adhering to antiviral regimens [8][9][10]. Across a range of settings and populations, depression has been associated with reduced probability of antiretroviral utilization [11,12].…”
mentioning
confidence: 99%